Association of genetic polymorphisms in PTEN and additional gene–gene interaction with risk of esophageal squamous cell carcinoma in Chinese Han population. Issue 8 (6th November 2015) - Xu, X.; Chen, G.; Wu, L.; Liu, L.
Summary: This study aims to investigate the association of five single nucleotide polymorphisms (SNPs) in the phosphatase and tensin homologue (PTEN) gene and additional role of gene–gene interaction with esophageal squamous cell carcinoma (ESCC), based on a Chinese case–control study. A total of 871 subjects (420 males and 451 females) were selected, including 425 ESCC cases and 446 controls. Five SNPs were selected for genotyping in the case–control study: rs2735343, rs555895, rs2299939, rs17431184 and rs701848. Logistic regression model was used to examine the association between five SNP and ESCC, and additional interaction among five SNP, odds ratio (OR) and 95% confident interval (95%CI) were calculated. All genotypes were distributed according to Hardy–Weinberg equilibrium in controls. The carriers of homozygous mutant of rs2735343 and rs701848 polymorphism revealed increased ESCC risk than those with wild‐type homozygotes, and OR (95%CI) were 1.27 (1.09–2.08) and 1.45 (1.17–1.98), respectively. We also found a potential gene–gene interaction between rs2735343 and rs701848 ( P = 0.0010), and a potential gene–gene interaction among all five SNP ( P = 0.0107) after covariates adjustment. Subjects with TC or CC of rs2735343 and TC or CC of rs701848 genotype have highest ESCC risk, compared to subjects with TT of rs2735343 and TT of rs701848 genotype, OR (95% CI) was 2.76 (1.37–3.45) after covariates adjustment. The carriers of homozygous mutant of rs2735343 and rs701848 polymorphism revealed increased ESCC risk. We also found a potential gene–gene interaction between rs2735343 and rs701848 and a potential gene–gene interaction among all five SNPs.